2011
DOI: 10.1007/s00414-011-0649-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of the new insertion–deletion polymorphism kit for forensic identification and parentage testing on the Czech population

Abstract: Insertion-deletion polymorphisms (INDELs) are diallelic markers derived from a single mutation event. Their low mutation frequency makes them suitable for forensic and parentage testing. The examination of INDELs thus combines advantages of both short tandem repeats (STR) and single nucleotide polymorphisms (SNP). This type of polymorphisms may be examined using as small amplicon size as SNP (about 100 bp) but could be analyzed by techniques used for routine STR analysis. For our population study, we genotyped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 11 publications
(19 reference statements)
1
21
1
2
Order By: Relevance
“…This study also revealed no significant difference in allele frequencies at most loci in Korean [3] and US Asian population [8] except for HLD118, HLD111, HLD81, and HLD39. However, statistically significant differences (after Bonferroni's correction; p<0.0026) were found with the populations of various ethnicities including Portuguese [4], Danes [5], Czechs [6], Germans [6], Spanish from central Spain [7], Basques [7], US Caucasians [8], US Afro-Americans [8], and US Hispanics [8]. For all 19 populations combined, Fst values arranged from 0.0093 to 0.2310.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…This study also revealed no significant difference in allele frequencies at most loci in Korean [3] and US Asian population [8] except for HLD118, HLD111, HLD81, and HLD39. However, statistically significant differences (after Bonferroni's correction; p<0.0026) were found with the populations of various ethnicities including Portuguese [4], Danes [5], Czechs [6], Germans [6], Spanish from central Spain [7], Basques [7], US Caucasians [8], US Afro-Americans [8], and US Hispanics [8]. For all 19 populations combined, Fst values arranged from 0.0093 to 0.2310.…”
mentioning
confidence: 82%
“…In this study, we analyzed 30 Indels in 952 Chinese individuals using the Investigator DIPplex® kit (Qiagen, Hilden, Germany). To test forensic efficiency and genetic relationship, we compared the data with other published population studies using the Investigator DIPplex® kit [2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are characterized by the presence or absence of a specific sequence of nucleotides [9][10][11][12]. Significative differences in allele frequencies of InDel markers, between different groups or populations, can be used as ancestry and eventually, evolutionary indicators [13].…”
Section: Introductionmentioning
confidence: 99%
“…They are relatively common throughout the human genome representing 15–20 % of all polymorphisms [1] with the total number estimated at about 2 million [2]. Short amplicon size (50–150 bp), low mutation rate (<2 × 10 −8 ), and capacity to multiplex (30–40 markers) and type using a single multiplexed PCR with fluorescently labeled primers followed by capillary electrophoresis (a current technology for human identification) [3–5] are the main advantages that make INDELs useful in forensic genetics applications including individual identification, kinship testing, population studies and ancient DNA analysis [68]. The Investigator DIPplex ® kit (Qiagen) contain components for the simultaneous amplification and analysis of 30 biallelic autosomal INDELs and amelogenin.…”
Section: Introductionmentioning
confidence: 99%